METHODS FOR TESTING DISCRIMINANT VALIDITY - Adriana ZAIŢ; Patricea Elena BERTEA (Management & Marketing)
The study presents three methods which can be used to assess discriminant validity for multi-item scales. Q-sorting is presented as a method that can be used in early stages of research, being more exploratory, while the chi-square difference test and the average variance extracted analysis are recommended for the confirmatory stages of research. The paper describes briefly the three methods and presents evidence from two surveys that aimed to develop a scale for measuring perceived risk in e-commerce.